Once again on spasticity in neurology (literature review) - M. A. Barabanova; O. V. Stoyanova; T. A. Petropavlovskaya; D. O. Kardailskaya (Инновационная медицина Кубани, 2019)
Now it is difficult to give exhaustive definition for spasticity taking into account its formation mechanisms as the neurobiology of the locomotion system is not studied regarding several aspects. The long term solution of this task will allow to define separate kinds of muscular hypertension, known for experts under the general name as a spasticity syndrome. At the same time for neurologists phenomenologically it is a rather clear question. Spastic paresis is the main reason of disability in neurologic patients as it develops in a great majority of diseases and damages of CNS. At the same time it limits physical activity in a patient by itself, but the expressed spasticity considerably aggravates motive violations, even more reducing functionality in a patient. While discussing approaches for spasticity treatment it is necessary to consider that this phenomenon is a very dynamic one. In this regard therapy of similar patients should be not only individual and carefully planned, but also constantly being monitored. Patients with spastic paresis require long-term treatment therefore it is necessary to reconsider the purposes and problems of therapy regularly, to define new boundaries and to specify old ones. It is especially important in a case with prolonged usage of muscle relaxants. The main treatment of a spastic muscular hypertension is a medical treatment. At the same time muscle relaxants are used both as monotherapy, and as a part of the general rehabilitation strategy. These drugs provide useful basic effect which allows to stack the paralyzed extremity in the most comfortable position or use the orthosis adequately. Thus, muscle relaxants impact a great number of neurophysiological and neurochemical mechanisms taking part in spasticity formation which provides their more significant efficiency.